Uji Sensitivitas Metode Pembobotan ROC, SWARA Terhadap Kriteria Karyawan Terbaik Dengan Menggunakan Metode SAW - Sudi Suryadi; Wahyu Azhar Ritonga; Taufiqqurrahman Nur Siagian; M Fauzi Romadhon Marpaung; Hariyanto Hariyanto; Sahbuki Ritonga; Raden Sri Ayu Ramadhana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Decision Support System or DSS is a branch of computer science to help a person or group in making a decision. In a decision, it has conditions such as there must be a choice candidate commonly referred to as an alternative and also criteria as an option in consideration, the criteria themselves are the most important part in determining the feasibility of a decision making, each criterion has its own value provided by the decision maker but it makes it is not clear on the decision to determine the value of the existing criteria, especially the criteria for evaluating the best employees, it is important to give the right weight value to the existing criteria. In assigning weight values, it is often wrong because the level of importance possessed by the criteria both have their own advantages, another problem in assigning weight values ​​is the type of weighting method that is very much also causing decision makers to be confused about choosing the right method so it is necessary to test the accuracy of the method. weighting in order to find the right results, the tests carried out in this study compared several weighting methods with the results as sensitivity tests such as ROC, SWARA as a weighting method and the SAW method as a widely used decision-making method. The results of the study found that the ROC-SAW value was 0.974, the value of the SWARA-SAW method was 0.9555. The highest accuracy value is obtained by the ROC-SAW method as a combination of methods that have higher sensitivity.